Rubber composition for tires

Wear resistance, wetland performance and low rolling in the prior art are solved by using specific configurations of end-modified styrene butadiene rubber, silica, thermoplastic resin and silane coupling agents in the tire rubber compositions. The problem of insufficient resistance achieves higher performance and processing performance.

CN119487117APending Publication Date: 2025-02-18THE YOKOHAMA RUBBER CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380051493.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-15
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing rubber compositions for tires have shortcomings in improving wear resistance, wetland performance and low rolling resistance, especially in reducing the temperature dependence of low rolling resistance and improving extrusion molding processability.

Method used

Using diene-based rubber containing terminally modified styrene butadiene rubber A and B, combined with silica, thermoplastic resin and silane coupling agent with thiol structure, the molecular weight distribution and component ratio of the rubber composition are adjusted to improve the Rubber integration and processing properties.

Benefits of technology

It achieves a significant improvement in wear resistance, wetland performance and low rolling resistance, while reducing the temperature dependence of low rolling resistance, and optimizing the extrusion molding processability to obtain high-quality tires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487117A_ABST
    Figure CN119487117A_ABST
Patent Text Reader

Abstract

Provided is a rubber composition for tires, which has excellent wear resistance, wet performance, and low rolling resistance, while having little temperature dependence on the low rolling resistance, and also having excellent extrusion processability. The present invention relates to a rubber composition which is characterized in that: 60-90 parts by mass of silica and 15-40 parts by mass of a thermoplastic resin are blended in 100 parts by mass of a diene rubber that contains 50-75% by mass of a terminal-modified SBR (A) having a weight-average molecular weight of 300,000-500,000 and a glass transition temperature of-50 DEG C or less, 0-50% by mass of a terminal-modified SBR (B) having a weight-average molecular weight of 600,000 or more, and 0-30% by mass of natural rubber; the total of the mass of the terminal-modified SBR (B) and the mass of the natural rubber is 1 / 3 or more of the mass of the terminal-modified SBR (A), and the weight-average molecular weight of the mixture comprising the terminal-modified SBR (B) and the natural rubber is 700,000 or more. The average glass transition temperature of the diene rubber is-50 DEG C or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rubber composition for a tire having excellent wear resistance, wet performance and low rolling resistance. Background Art

[0002] Tires are required to have high levels of wear resistance, wet performance and low rolling resistance. In addition, with the improvement of low rolling resistance, it is required to show low rolling resistance even when the tire temperature is low, that is, the temperature dependence of low rolling resistance is small.

[0003] Patent document 1 proposes to improve low rolling resistance, wet grip performance and wear resistance by adding 2 to 50 parts by weight of an aromatic modified terpene resin having a softening point of 100°C or more and two specific silicas to 100 parts by weight of a diene rubber containing 5 to 50% by weight of a terminal modified solution polymerized styrene butadiene rubber having a glass transition temperature of -50°C or less, and preparing a tire rubber composition. However, the invention described in patent document 1 may not necessarily achieve sufficient effects in reducing low rolling resistance and its temperature dependence. In addition, in the invention described in patent document 1, the molding processability is sometimes reduced and needs to be improved. This is because the terminal-modified solution-polymerized styrene-butadiene rubber with a low glass transition temperature tends to have a low styrene content, and the rubber conformability during mixing is poor. In addition, from the perspective of increasing the polymerization rate and terminal modification efficiency, the molecular weight of the terminal-modified solution-polymerized styrene-butadiene rubber is sometimes designed to be relatively low, and there is a tendency for the green rubber strength and elongation to decrease. Therefore, for example, during extrusion processing, residual rubber appears in the extruder, and the surface unevenness of the extruded product becomes larger, resulting in poor processing accuracy. In addition, if a silane coupling agent with high reactivity with silica and rubber is used, the plasticity of the rubber composition is reduced, and the quality of the extruded product may also be reduced.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-227375 Summary of the invention

[0007] Problems to be solved by the invention

[0008] An object of the present invention is to provide a rubber composition for a tire which can improve wear resistance, wet performance and low rolling resistance to levels higher than those of the prior art, reduce the temperature dependence of low rolling resistance and also has excellent extrusion molding processability.

[0009] Solution

[0010] The tire rubber composition of the present invention which achieves the above-mentioned object is characterized in that, in 100 parts by mass of a diene rubber containing terminal-modified styrene-butadiene rubber A and containing natural rubber and / or terminal-modified styrene-butadiene rubber B, 60 to 90 parts by mass of silica and 15 to 40 parts by mass of a thermoplastic resin are blended, and a silane coupling agent having a mercapto structure is blended in an amount of 2 to 15% by mass relative to the mass of the silica, wherein the terminal-modified styrene-butadiene rubber A has a weight average molecular weight of 300,000 to 500,000 and a glass transition temperature of -50°C or less, and the terminal-modified styrene-butadiene rubber B has a weight average molecular weight of 300,000 to 500,000 and a glass transition temperature of -50°C or less. The weight average molecular weight of the modified styrene butadiene rubber B is 600,000 or more, the weight average molecular weight of the mixture composed of the terminal modified styrene butadiene rubber B and the natural rubber is 700,000 or more, the average glass transition temperature of the diene rubber is -50°C or less, in 100% by mass of the diene rubber, the terminal modified styrene butadiene rubber A is 50 to 75% by mass, the natural rubber is 0 to 30% by mass, and the total mass of the terminal modified styrene butadiene rubber B and the natural rubber is 1 / 3 or more of the mass of the terminal modified styrene butadiene rubber A.

[0011] Effects of the Invention

[0012] The tire rubber composition of the present invention can improve wear resistance, wet performance, and low rolling resistance to above the conventional levels due to the above-mentioned structure, can reduce the temperature dependence of low rolling resistance, and is also excellent in extrusion molding processability.

[0013] The terminal-modified styrene-butadiene rubber (B) preferably has a unimodal molecular weight distribution curve when measured by gel permeation chromatography, and its molecular weight distribution (PDI) is preferably less than 1.7. In addition, it is preferred that 0 to 50% by mass of the terminal-modified styrene-butadiene rubber (B) is contained in 100% by mass of the diene rubber.

[0014] The thermoplastic resin contains 25% by mass or more of a terpene resin, and when the terpene resin contains a unit derived from α-pinene, the content of the unit derived from α-pinene is preferably 60% by mass or less. In addition, the glass transition temperature of the thermoplastic resin is preferably 40°C to 120°C. Alternatively, the thermoplastic resin is at least one resin selected from the following resins and resins in which at least a part of the double bonds of these resins are hydrogenated, and the glass transition temperature of the thermoplastic resin is preferably 40 to 120°C, and the resin is terpene, modified terpene, rosin, rosin ester, or a resin composed of at least one selected from C5 component and C9 component.

[0015] A tire having a tread portion formed from the above-mentioned tire rubber composition can improve wear resistance, wet performance and low rolling resistance to above the existing level, and the temperature dependence of the low rolling resistance is small, and a tire with good extrusion molding processability and excellent quality can be stably obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a cross-sectional view in the tire meridian direction illustrating an embodiment of a tire formed using the rubber composition for a tire of the present invention. DETAILED DESCRIPTION

[0017] The rubber composition for a tire of the present invention can be applied to a tread portion or a sidewall portion of a tire. In addition, the tire may be either a pneumatic tire or a non-pneumatic tire. Figure 1 1 is a cross-sectional view showing an example of an embodiment of a pneumatic tire. The pneumatic tire includes a tread portion 1 , a sidewall portion 2 , and a bead portion 3 .

[0018] exist Figure 1 In the embodiment, two carcass layers are arranged between the left and right bead portions 3, and the reinforcing cords arranged at a predetermined interval along the circumferential direction of the tire and extending in the radial direction of the tire are buried in the rubber layer in the carcass layer, and the two ends of the carcass layer are folded back from the inner side of the tire axial direction to the outer side in a manner of sandwiching the bead filler 6 around the bead core 5 buried in the bead portion 3. An inner liner 7 is arranged on the inner side of the carcass layer 4. On the outer peripheral side of the carcass layer 4 of the tread portion 1, two belt layers 8 are arranged in which the reinforcing cords extending obliquely along the circumferential direction of the tire are arranged at a predetermined interval along the axial direction of the tire and buried in the rubber layer. The reinforcing cords of the two belt layers 8 cross each other in an oblique direction relative to the circumferential direction of the tire between the layers, that is, the cord directions cross each other in opposite directions. A belt covering layer 9 is arranged on the outer peripheral side of the belt layer 8. The belt covering layer 9 can be either a full covering type covering the entire belt layer or an edge type covering the ends of the belt layer in the tire width direction, or a combination of the two types. The tread portion 1 is disposed on the outer peripheral side of the belt cover layer 9. The tread portion 1 is composed of a tread cap 10a and a tread base 10b. The tire rubber composition of the present invention is preferably used for the tread portion 1 or the sidewall portion 2, and more preferably for the tread cap 10a or the tread base 10b.

[0019] In the tire rubber composition of the present invention, the diene rubber contains terminal-modified styrene-butadiene rubber (A) and contains natural rubber and / or terminal-modified styrene-butadiene rubber (B). That is, as the diene rubber, the terminal-modified styrene-butadiene rubber (A) must be contained, and at least one selected from natural rubber and terminal-modified styrene-butadiene rubber (B) is contained.

[0020] The terminal-modified styrene butadiene rubber (A) has a weight average molecular weight of 300,000 to 500,000 and a glass transition temperature of -50°C or lower. By including the terminal-modified styrene butadiene rubber (A), rolling resistance can be reduced, temperature dependence thereof can be reduced, and wear resistance can be improved.

[0021] The glass transition temperature (hereinafter sometimes referred to as "Tg") of the terminal-modified styrene-butadiene rubber (A) is preferably -75°C to -50°C, more preferably -70°C to -55°C. In the present specification, Tg can be measured as the temperature of the midpoint of the phase transition region based on a thermal diagram obtained by differential scanning calorimetry (DSC) at a heating rate of 20°C / min. In addition, when the diene rubber is an oil-extended product, the Tg of the diene rubber in a state without the oil-extending component (oil) is taken.

[0022] The weight average molecular weight of the terminal modified styrene butadiene rubber (A) is preferably 350,000 to 500,000, more preferably 400,000 to 500,000. By making the weight average molecular weight of the terminal modified styrene butadiene rubber (A) within such a range, the rolling resistance can be further reduced. In this article, the weight average molecular weight can be a polystyrene conversion value measured by gel permeation chromatography (GPC).

[0023] The styrene content of the terminal-modified styrene-butadiene rubber (A) is preferably 5 to 25% by mass, more preferably 10 to 20% by mass. When the styrene content is 5% by mass or more, the wet performance becomes higher, and when the styrene content is 25% by mass or less, the temperature dependence of the rolling resistance becomes smaller, so it is preferred. In this specification, the styrene content is expressed by 1 Value measured by H-NMR.

[0024] The vinyl content of the terminal-modified styrene butadiene rubber (A) is preferably 10 to 45%, more preferably 15 to 40%. When the vinyl content is 10% by mass or more, the temperature dependence of the rolling resistance becomes small, and when the vinyl content is 45% by mass or less, the wear resistance is improved, so it is preferred. In this specification, the vinyl content is expressed by 1 Value measured by H-NMR.

[0025] At least one end of the terminal-modified styrene butadiene rubber (A) is modified by a functional group. Examples of the functional group include epoxy, carboxyl, amino, hydroxyl, alkoxy, silyl, alkoxysilyl, amide, oxysilyl, silanol, isocyanate, isothiocyanate, carbonyl, aldehyde, etc. In addition, as the functional group of the terminal-modified styrene butadiene rubber (A), preferably a functional group having a polyorganosiloxane structure or an aminosilane structure is listed. The terminal-modified styrene butadiene rubber (A) has a functional group or an alkoxy group having a polyorganosiloxane structure or an aminosilane structure, which can make the dispersibility of silica good, and has low rolling resistance, wear resistance and excellent wet performance.

[0026] The terminal modified styrene butadiene rubber (A) is 50 to 75% by mass, preferably 50 to 70% by mass, and more preferably 55 to 70% by mass in 100% by mass of the diene rubber. When the terminal modified styrene butadiene rubber (A) is less than 50% by mass, the effect of reducing rolling resistance or improving wear resistance cannot be fully obtained. In addition, if it exceeds 75% by mass, wet performance is reduced and extrusion molding processability is also deteriorated.

[0027] The tire rubber composition contains at least one selected from the group consisting of terminal-modified styrene-butadiene rubber (B) and natural rubber. That is, the tire rubber composition may contain both terminal-modified styrene-butadiene rubber (B) and natural rubber, or may contain either terminal-modified styrene-butadiene rubber (B) or natural rubber.

[0028] The weight average molecular weight of the terminal modified styrene butadiene rubber (B) is 600,000 or more, and is determined in such a way that the weight average molecular weight of the mixture composed of the terminal modified styrene butadiene rubber (B) and the natural rubber is 700,000 or more. By containing the terminal modified styrene butadiene rubber (B), the rolling resistance can be reduced and its temperature dependence is also reduced. The weight average molecular weight of the terminal modified styrene butadiene rubber (B) is preferably 600,000 to 1.5 million, and more preferably 700,000 to 1.3 million. By making the weight average molecular weight of the terminal modified styrene butadiene rubber (B) within such a range, the low rolling resistance and temperature dependence of the rubber composition can be excellent.

[0029] The weight average molecular weight of the mixture consisting of terminal modified styrene butadiene rubber (B) and natural rubber is 700,000 or more, preferably 700,000 to 1.3 million, and more preferably 700,000 to 1.2 million. By making the weight average molecular weight of the mixture consisting of terminal modified styrene butadiene rubber (B) and natural rubber within such a range, it is possible to suppress the rubber residue in the extruder or the concavo-convexity on the surface of the extrudate during extrusion molding. The mixture consisting of terminal modified styrene butadiene rubber (B) and natural rubber is a blend that can be prepared into the same ratio as the tire rubber composition. Its weight average molecular weight can be measured by GPC, or it can be calculated as a weighted average value based on the weight average molecular weight of each terminal modified styrene butadiene rubber (B) and natural rubber and the mass ratio of the rubber composition.

[0030] The molecular weight distribution curve of the terminal-modified styrene-butadiene rubber (B) when measured by gel permeation chromatography may have a unimodal shape, and preferably its molecular weight distribution (PDI) is less than 1.7. When the molecular weight distribution curve of the terminal-modified styrene-butadiene rubber (B) is unimodal, the uniformity of the molecules becomes higher, and it can be evenly distributed and dispersed in the diene rubber, and the affinity with silica is higher. The molecular weight distribution (PDI) is the ratio (Mw / Mn) of the weight average molecular weight (Mw) and the number average molecular weight (Mn) measured by gel permeation chromatography. When the molecular weight distribution is less than 1.7, the molecular uniformity becomes higher, and it can be evenly distributed and dispersed in the diene rubber, and the affinity with silica is high, just like the molecular weight distribution curve has a unimodal shape. The molecular weight distribution (PDI) is more preferably greater than 1.0 and less than 1.7, and more preferably 1.1 to 1.6. Such a terminal-modified styrene-butadiene rubber (B) is preferably obtained by continuous polymerization.

[0031] In this specification, when the molecular weight distribution curve, weight average molecular weight (Mw) and number average molecular weight (Mn) of the terminal-modified styrene butadiene rubber (B) are measured by gel permeation chromatography, the following conditions can be cited, for example. In addition, the terminal-modified styrene butadiene rubber (A) and natural rubber can also be measured in the same manner.

[0032] Apparatus: Gel permeation chromatography [GPC: HLC-8020 manufactured by Tosoh Corporation]

[0033] Chromatographic column: GMH-HR-H manufactured by Tosoh Corporation (2 connected in series)

[0034] Measurement temperature: 40℃

[0035] Carrier gas: Helium

[0036] Flow rate: 5mmol / L

[0037] Sample: 10 mg dissolved in 10 mL THF

[0038] Injection volume: 10 μL

[0039] Detector: Differential refractometer (RI-8020)

[0040] At least one end of the terminal-modified styrene butadiene rubber (B) is modified by a functional group. As its functional group, it can be appropriately selected from the functional groups exemplified as the functional groups of the terminal-modified styrene butadiene rubber (A). The functional group of the terminal-modified styrene butadiene rubber (B) may be the same as or different from the functional group of the terminal-modified styrene butadiene rubber (A). As the functional group of the terminal-modified styrene butadiene rubber (B), for example, a modified group having a polyorganosiloxane structure or an aminosilane structure, an alkoxysilyl group, an amino group, a hydroxyl group, etc. can be preferably cited.

[0041] The Tg of the terminal-modified styrene butadiene rubber (B) is preferably -55°C to -15°C, more preferably -50°C to -20°C, and further preferably -45°C to -25°C. In addition, the Tg of the terminal-modified styrene butadiene rubber (B) is preferably higher than the Tg of the terminal-modified styrene butadiene rubber (A). By setting the Tg of the terminal-modified styrene butadiene rubber (B) within such a range, wet performance can be improved, which is preferred.

[0042] The styrene content of the terminal-modified styrene-butadiene rubber (B) is preferably 20 to 45% by mass, more preferably 25 to 40% by mass. When the styrene content is 20% by mass or more, the effect of improving wet performance is greater, and when the styrene content is 45% by mass or less, the effect on wear resistance can be suppressed, so it is preferred.

[0043] The vinyl content of the terminal-modified styrene butadiene rubber (B) is preferably 15 to 50%, more preferably 20 to 45%. A vinyl content of 15% by mass or more improves wet performance, while a vinyl content of 50% by mass or less can suppress the effect on wear resistance, which is preferred.

[0044] The content of the terminal-modified styrene butadiene rubber (B) is determined in such a way that the total mass of the terminal-modified styrene butadiene rubber (B) and the natural rubber is 1 / 3 or more of the mass of the terminal-modified styrene butadiene rubber (A). The ratio of the total mass of the terminal-modified styrene butadiene rubber (B) and the natural rubber to the mass of the terminal-modified styrene butadiene rubber (A) is preferably 1 / 3 to 1 / 1, and more preferably 2 / 5 to 1 / 1. By making the total mass of the terminal-modified styrene butadiene rubber (B) and the natural rubber within such a range, it is possible to suppress the rubber from remaining in the extruder, and it is possible to suppress the increase of the unevenness of the surface of the extruded product.

[0045] The content of the terminal-modified styrene-butadiene rubber (B) is preferably 0 to 50% by mass, more preferably 10 to 40% by mass, and even more preferably 20 to 30% by mass in 100% by mass of the diene rubber.

[0046] The rubber composition for tires contains 0 to 30% by mass, preferably 10 to 25% by mass, and more preferably 15 to 25% by mass of natural rubber in 100% by mass of diene rubber. In addition, as mentioned above, the content of natural rubber is determined in such a way that the total mass of the terminal-modified styrene-butadiene rubber (B) and the natural rubber is more than 1 / 3 of the mass of the terminal-modified styrene-butadiene rubber (A). By adding natural rubber, the green strength is improved, and it is difficult for rubber to remain in the extruder. In addition, by making the natural rubber less than 30% by mass, the dispersibility of silica becomes good, which can improve low rolling performance and wet performance. There is no particular limitation on the type of natural rubber, and rubber commonly used in rubber compositions for tires can be used.

[0047] As described above, the weight average molecular weight of the natural rubber is determined so that the weight average molecular weight of the mixture consisting of the terminal-modified styrene-butadiene rubber (B) and the natural rubber is 700,000 or more. The details are as described above.

[0048] In the rubber composition for tires, the average glass transition temperature of the diene rubber is -50°C or less, preferably -65°C to -50°C, and more preferably -60°C to -50°C. By making the average glass transition temperature of the diene rubber within such a range, it is possible to achieve a balance between the temperature dependence of the rolling resistance and the wet performance at a high level. The average glass transition temperature of the diene rubber can be calculated as a weighted average of the glass transition temperatures of the rubbers constituting the diene rubber and their respective mass fractions.

[0049] The tire rubber composition contains 60 to 90 parts by mass of silica, preferably 65 to 85 parts by mass, and more preferably 70 to 80 parts by mass of silica in 100 parts by mass of diene rubber. By adding silica, low rolling resistance and wet performance can be improved. When silica is less than 60 parts by mass, the effect of improving wet performance cannot be fully obtained. In addition, when silica exceeds 90 parts by mass, there is a tendency for low rolling resistance to deteriorate.

[0050] As silica, silica commonly used in tire rubber compositions can be used, for example, wet silica, dry silica, carbon-silica (dual phase filler) in which silica is supported on the surface of carbon black, silica surface-treated with a compound reactive or compatible with both silica and rubber, such as a silane coupling agent or polysiloxane, etc. Among them, wet silica having hydrous silicic acid as a main component is preferred.

[0051] In addition, by combining a silane coupling agent having a mercapto structure with silica, the dispersibility of silica is improved and the wetland performance is further improved, so it is preferred. In this specification, a silane coupling agent having a mercapto structure refers to a silane coupling agent having a mercapto group (-SH) and a silane coupling agent having a -SC(=O)- bond in the main chain. Here, the -SC(=O)- bond is easily decomposed into a mercapto group (-SH) at high temperatures. The silane coupling agent is mixed with 2 to 15% by mass relative to the mass of silica, preferably 3 to 12% by mass, and more preferably 3 to 9% by mass. When the silane coupling agent is less than 2% by mass of the mass of silica, the effect of improving the dispersibility of silica cannot be fully obtained. In addition, if the silane coupling agent exceeds 15% by mass, there is a tendency for the diene rubber component to gel easily, so the desired effect cannot be obtained.

[0052] Preferred examples of the silane coupling agent having a mercapto structure include a silane coupling agent represented by the average composition formula of the following formula (1) and a silane coupling agent represented by the following general formula (2).

[0053] (A) a (B) b (C) c (D) d (R 1 ) e SiO (4-2a-b-c-d-e) / 2 …(1)

[0054] In formula (1), A represents a divalent organic group containing a thioether group, B represents a monovalent hydrocarbon group having 5 to 10 carbon atoms, C represents a hydrolyzable group, D represents an organic group containing a mercapto group, and R 1 represents a monovalent hydrocarbon group having 1 to 4 carbon atoms, where a to e satisfy the relationship 0≤a<1, 0<b<1, 0<c<3, 0<d<1, 0≤e<2, 0<2a+b+c+d+e<4)

[0055]

[0056] (In formula (2), R 2 ~R 4independently represent an alkyl group or an alkoxy group having 1 to 6 carbon atoms, at least one of which represents an alkoxy group, R 5 represents an alkyl group having 3 to 10 carbon atoms. )

[0057] The silane coupling agent represented by the above formula (1) preferably has a polysiloxane skeleton. The polysiloxane skeleton may be a linear, branched, or three-dimensional structure, or a combination thereof.

[0058] In the above formula (1), the hydrocarbon group B is a monovalent hydrocarbon group having 5 to 10 carbon atoms, preferably 6 to 10 carbon atoms, and more preferably 8 to 10 carbon atoms. Examples thereof include hexyl, octyl, and decyl. In this way, the mercapto group can be protected, the Mooney scorch time can be prolonged, the processability (scorch resistance) can be improved, and the low rolling resistance can be improved. The subscript b of the hydrocarbon group B is greater than 0, preferably 0.10≤b≤0.89.

[0059] In the above formula (1), the organic group A represents a divalent organic group containing a thioether group (hereinafter also referred to as "the organic group containing a thioether group"). By having an organic group containing a thioether group, low heat generation and processability (particularly, maintenance and extension of Mooney scorch time) are more excellent. Therefore, the subscript a of the organic group A containing a thioether group may be greater than 0, and more preferably 0<a≤0.50. The organic group A containing a thioether group may have a heteroatom, such as an oxygen atom, a nitrogen atom, or a sulfur atom.

[0060] Among them, the thioether group-containing organic group A is preferably a group represented by the following formula (3).

[0061] *-(CH2) n -Sx-(CH2) n -*…(3)

[0062] (In the above formula (3), n represents an integer of 1 to 10, x represents an integer of 1 to 6, and * represents a bonding position.)

[0063] Specific examples of the thioether group-containing organic group A represented by the general formula (3) include the following groups.

[0064] *-CH2-S2-CH2-*, *-C2H4-S2-C2H4-*, *-C3H6-S2-C3H6-*, *-C4H8-S2-C4H8-* ,*-CH2-S4-CH2-*,*-C2H4-S4-C2H4-*,*-C3H6-S4-C3H6-*,*-C4H8-S4-C4H8-*

[0065] The silane coupling agent composed of the polysiloxane represented by the average composition formula of the general formula (1) has excellent affinity and / or reactivity with silicon dioxide due to the presence of a hydrolyzable group C. The subscript c of the hydrolyzable group C in the general formula (1) is preferably 1.2≤c≤2.0 for the reasons of low heat generation, better processability (scorch resistance) and better dispersibility of silicon dioxide. Specific examples of the hydrolyzable group C include, for example, alkoxy, phenoxy, carboxyl, alkenyloxy, etc. As the hydrolyzable group C, from the viewpoint of making the dispersibility of silicon dioxide good and making the processability (scorch resistance) better, the group represented by the following general formula (4) is preferred.

[0066] *-OR 6 ···(4)

[0067] In the above general formula (4), * represents the binding position. 6 It represents an alkyl group having 1 to 20 carbon atoms, an aryl group having 6 to 10 carbon atoms, an aralkyl group having 6 to 10 carbon atoms (arylalkyl group), or an alkenyl group having 2 to 10 carbon atoms, and among them, an alkyl group having 1 to 5 carbon atoms is preferred.

[0068] Specific examples of the alkyl group having 1 to 20 carbon atoms include, for example, methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, octadecyl, etc. Specific examples of the aryl group having 6 to 10 carbon atoms include, for example, phenyl, tolyl, etc. Specific examples of the aralkyl group having 6 to 10 carbon atoms include, for example, benzyl, phenylethyl, etc. Specific examples of the alkenyl group having 2 to 10 carbon atoms include, for example, ethenyl, propenyl, pentenyl, etc.

[0069] The silane coupling agent composed of polysiloxane represented by the average composition formula of the general formula (1) can interact and / or react with the diene rubber by having an organic group D containing a mercapto group, thereby making the low heat generation excellent. The subscript d of the organic group D containing a mercapto group can be 0.1≤d≤0.8. As the organic group D containing a mercapto group, from the viewpoint of making the dispersibility of silica good and the processability (scorch resistance) better, it is preferably a group represented by the following general formula (5).

[0070] *-(CH2) m -SH···(5)

[0071] In the above general formula (5), m represents an integer of 1 to 10, and preferably an integer of 1 to 5. In the formula, * represents a bonding position.

[0072] Specific examples of the group represented by the general formula (5) include the following groups:

[0073] *-CH2SH, *-C2H4SH, *-C3H6SH, *-C4H8SH, *-C5H 10 SH, *-C6H 12 SH, *-C7H 14 SH, *-C8H 16 SH, *-C9H 18 SH, *-C 10 H 20 SH

[0074] In the above general formula (1), R 1 represents a monovalent hydrocarbon group having 1 to 4 carbon atoms. 1 , for example, methyl, ethyl, propyl, and butyl can be mentioned.

[0075] In the silane coupling agent represented by the general formula (2), R 2 ~R 4 R independently represents an alkyl group or an alkoxy group having 1 to 6 carbon atoms. 2 ~R 4 At least one of the R represents an alkoxy group. The alkyl group and the alkoxy group may be straight chain or branched. 2 ~R 4 They may be the same as or different from each other. 2 ~R 4 For example, a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a pentyloxy group, a hexyl group, a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group etc. are mentioned.

[0076] In the general formula (2), R 5 represents an alkyl group having 3 to 10 carbon atoms. 5 The group may be straight-chain or branched, and examples thereof include n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, 1,1-dimethylpropyl, n-hexyl, 1,1-dimethylbutyl, n-heptyl, 1,1-dimethylpentyl, n-octyl, 1,1-dimethylhexyl, n-nonyl, and n-decyl.

[0077] Examples of the silane coupling agent represented by the general formula (2) include 3-octanoylthio-1-propyltriethoxysilane, 3-octanoylthio-1-propylethyldiethoxysilane, 3-hexanoylthiopropyltriethoxysilane, 3-decanoylthiopropyltriethoxysilane, 3-hexanoylthiopropyltrimethoxysilane, and 3-decanoylthiopropyltrimethoxysilane.

[0078] By adding fillers other than silica to the rubber composition for tires, the strength of the rubber composition can be improved and the durability of the tire can be ensured. Examples of other fillers include inorganic fillers such as carbon black, calcium carbonate, magnesium carbonate, talc, clay, aluminum oxide, aluminum hydroxide, titanium oxide, calcium sulfate, mica, and barium sulfate, and organic fillers such as cellulose, lecithin, lignin, and dendrimers.

[0079] Among them, by combining carbon black, the strength of the rubber composition can be made excellent, thereby improving wear resistance. As carbon black, furnace black, acetylene black, thermal black, channel black, graphite and other carbon blacks can also be combined. Among them, furnace black is preferred, and as its specific example, SAF, ISAF, ISAF-HS, ISAF-LS, IISAF-HS, HAF, HAF-HS, HAF-LS, FEF and the like can be listed. These carbon blacks can be used alone, or two or more can be used in combination. In addition, surface treated carbon blacks formed by chemically modifying these carbon blacks with various acid compounds can also be used.

[0080] The tire rubber composition is formulated with 15 to 40 parts by mass, preferably 15 to 35 parts by mass, and more preferably 17 to 30 parts by mass of a thermoplastic resin in 100 parts by mass of a diene rubber. By formulating the thermoplastic resin, the wear resistance is improved, the Tg of the rubber composition is increased, and the wet performance is improved. If the thermoplastic resin is less than 15 parts by mass, the effect of improving the wear resistance and wet performance cannot be fully obtained. When the thermoplastic resin exceeds 40 parts by mass, the rolling resistance increases.

[0081] Thermoplastic resins are resins that are usually added to tire rubber compositions, have a molecular weight of several hundred to several thousand, and have the function of imparting adhesiveness to tire rubber compositions. As thermoplastic resins, it is preferably selected from, for example, the following resins: terpenes, modified terpenes, rosins, rosin esters, and resins composed of at least one selected from C5 components and C9 components, and resins in which at least a portion of the double bonds of these resins are hydrogenated. Examples of natural resins include terpene resins, modified terpene resins, rosin resins, rosin ester resins, and synthetic resins such as petroleum resins composed of C5 components and C9 components such as C5 resins, C9 resins, and C5C9 copolymer resins, coal resins, phenolic resins, and xylene resins.

[0082] Examples of the terpene resins include α-pinene resins, β-pinene resins, limonene resins, hydrogenated limonene resins, dipentene resins, terpene phenol resins, terpene styrene resins, aromatic modified terpene resins, hydrogenated terpene resins, etc. Examples of the rosin resins include gum rosin, tall oil rosin, wood rosin, hydrogenated rosin, disproportionated rosin, polymerized rosin, modified rosins such as maleated rosin and fumarated rosin, ester derivatives of these rosins such as glycerol esters, pentaerythritol esters, methyl esters and triethylene glycol esters, and rosin-modified phenolic resins.

[0083] In addition, in the present invention, the thermoplastic resin preferably contains 25% by mass or more of a terpene resin. When the thermoplastic resin contains 25% by mass or more of a terpene resin, wet performance can be improved while maintaining low rolling resistance. In addition, the terpene resin may contain a unit derived from α-pinene, and the content of the unit derived from α-pinene is preferably limited to 60% by mass or less in 100% by mass of the terpene resin.

[0084] Examples of petroleum-based resins include aromatic hydrocarbon resins or saturated or unsaturated aliphatic hydrocarbon resins, such as C5 petroleum resins (aliphatic petroleum resins obtained by polymerizing fractions of isoprene, 1,3-pentadiene, cyclopentadiene, methylbutene, pentene, etc.), C9 petroleum resins (aromatic petroleum resins obtained by polymerizing fractions of α-methylstyrene, o-vinyltoluene, m-vinyltoluene, p-vinyltoluene, etc.), and C5C9 copolymer petroleum resins.

[0085] The glass transition temperature of the thermoplastic resin is preferably 40°C to 120°C, more preferably 45°C to 115°C, and even more preferably 50°C to 110°C. By setting the glass transition temperature of the thermoplastic resin to 40°C or higher, dry grip performance can be improved, so it is preferred. Furthermore, by setting it to 120°C or lower, wear resistance is improved, so it is preferred. The glass transition temperature of the thermoplastic resin can be measured by the above method.

[0086] In the rubber composition for tires, in addition to the above-mentioned components, various compounding agents commonly used in rubber compositions for tires such as vulcanization or crosslinking agents, vulcanization accelerators, anti-aging agents, processing aids, plasticizers, thermosetting resins, etc. can be mixed according to conventional methods. Such compounding agents can be mixed by a general method to make a rubber composition for vulcanization or crosslinking. The amount of these compounding agents can be the general amount in the past as long as it does not violate the purpose of the present invention. The rubber composition for tires can be prepared by mixing the above-mentioned components using a known rubber mixing machine, such as a Banbury mixer, a kneading machine, a roller, etc.

[0087] The tire rubber composition is suitable for forming a tread portion or a sidewall portion of a tire, and is particularly suitable for forming a tread portion of a tire. The tire obtained thereby can improve the wear resistance, wet performance and low rolling resistance to above the existing level, and can stably obtain a tire having low temperature dependence of low rolling resistance, good extrusion molding processability and excellent quality.

[0088] The present invention will be further described below by way of examples, but the scope of the present invention is not limited to these examples.

[0089] Example

[0090] When preparing 31 kinds of rubber compositions for tires (standard examples, examples 1 to 16, comparative examples 1 to 14) having the common additive formulation shown in Table 5 and prepared from the formulations shown in Tables 1 to 4, the components other than sulfur and vulcanization accelerator were weighed separately, and after kneading for 5 minutes in a 1.7-liter closed Banbury mixer, the masterbatch was released outside the mixer and cooled at room temperature. The masterbatch was supplied to the Banbury mixer, sulfur and vulcanization accelerator were added and mixed to obtain a rubber composition for tires. In the table, SBR (B) -1 and SBR (B) -2 were 25 parts by mass, and SBR (B) -3 was 20 parts by mass of oil-extended products, so the compounding amount after removing the oil-extending component is recorded in the brackets below. In addition, the ratio of the total mass of the terminal-modified styrene butadiene rubber (B) and the natural rubber to the mass of the terminal-modified styrene butadiene rubber (A) is recorded in the column "Mass ratio (SBR (B) + NR) / SBR (A)", and the weight average molecular weight of the mixture composed of the terminal-modified styrene butadiene rubber (B) and the natural rubber is recorded in the column "Weight average molecular weight of (SBR (B) + NR)". In addition, the average glass transition temperature of the diene rubber is recorded in the column "Average Tg of diene rubber". In addition, the additive formulations in Table 5 are recorded in parts by mass relative to 100 parts by mass of the diene rubber described in Tables 1 to 4.

[0091] The tire rubber composition obtained above was vulcanized at 160°C for 20 minutes in a mold of a predetermined shape to prepare an evaluation sample. The obtained evaluation sample was used to measure the dynamic viscoelasticity (loss tangent tanδ at 0°C, 20°C and 60°C) and wear resistance by the following method. In addition, the extrusion processability of the tire rubber composition obtained was evaluated by the following method.

[0092] Dynamic viscoelasticity (loss tangent tanδ at 0℃, 20℃ and 60℃)

[0093] Using a viscoelasticity spectrometer manufactured by Iwamoto Seisakusho Co., Ltd., the dynamic viscoelasticity of the evaluation sample of the tire rubber composition was measured under the conditions of a tensile deformation strain rate of 10±2%, a frequency of 20 Hz, and temperatures of 0°C, 20°C, and 60°C. The result of the loss tangent tanδ obtained at 0°C was expressed as an index when the value of the standard example was taken as an index of 100, as shown in the "Wetland Performance" column of Tables 1 to 4. The larger the index, the larger the tanδ at 0°C and the better the wetland performance. In this specification, a value of 108 or more is considered to be good in wetland performance. The reciprocal of the loss tangent tanδ obtained at 60°C was calculated and expressed as an index when the value of the standard example was taken as an index of 100, as shown in the "Rolling Resistance" column of Tables 1 to 4. The larger the index, the smaller the tanδ at 60°C and the better the rolling resistance performance. In this specification, a value of 103 or more is considered to be good in low rolling resistance performance. Then, the loss tangent tanδ at 60°C was divided by the loss tangent tanδ at 20°C, and the value was expressed as an index with the value of the standard example as 100, as shown in the "Temperature Dependence of Rolling Resistance" column of Tables 1 to 4. The larger the index, the smaller the temperature dependence of the rolling resistance performance. In this specification, when the index is 105 or more, it is considered that the temperature dependence of the low rolling resistance performance is small and excellent.

[0094] Wear resistance

[0095] The evaluation samples of the obtained tire rubber composition were measured for wear amount using a Lamborn wear tester (manufactured by Iwamoto Seisakusho Co., Ltd.) based on JIS K6264 under the conditions of a load of 15.0 kg (147.1 N) and a slip rate of 25%. The reciprocal of each result was calculated, and the index when the reciprocal of the wear amount of the standard example was taken as 100 was recorded in the "wear resistance" column of Tables 1 to 4. The larger the index, the less the wear amount and the better the wear resistance.

[0096] Extrusion processability

[0097] Using the obtained tire rubber composition, extrusion samples were prepared using a Garvey die according to ASTM D230-77, and the appearance (edge ​​sharpness and surface skin smoothness) of each extruded sample at 20 cm was visually evaluated according to the following criteria, and the results are recorded in the "Extrusion Processability" column of Tables 1 to 4. If the score was 1 or 2, it was judged that the extrusion processability was excellent.

[0098] 1: No edge cracks and the surface is smooth.

[0099] 2: The edge has more than 1 but less than 5 cracks, and the surface is smooth.

[0100] 3: The edge is cracked in more than 6 but less than 10 places, and no fuzzing or perforation is found on the surface.

[0101] 4: There are more than 11 cracks on the edge, or the surface is fuzzy or perforated.

[0102]

[0103]

[0104]

[0105]

[0106] The types of raw materials used in Tables 1 to 4 are as follows.

[0107] SBR (A)-1: terminal modified styrene butadiene rubber with polyorganosiloxane structure, Nipol NS612 produced by Zeon Co., Ltd., Japan, glass transition temperature of -60 ° C, weight average molecular weight of 450,000, styrene content of 15% by mass, vinyl content of 31%, non-oil-filled product.

[0108] SBR (A)-2: a terminal-modified styrene butadiene rubber having a polyorganosiloxane structure obtained by the following polymerization method, having a glass transition temperature of -70°C, a weight average molecular weight of 450,000, a styrene content of 18% by mass, a vinyl content of 13%, and being a non-oil-extended product.

[0109] SBR-1: Styrene butadiene rubber, HPR850 produced by JSR, glass transition temperature of -25°C, weight average molecular weight of 370,000, styrene content of 27.0% by mass, vinyl content of 58.8%, non-oil-filled product.

[0110] SBR (B) -1: terminal modified styrene butadiene rubber with polyorganosiloxane structure, NS560 produced by Zeon Co., Ltd. of Japan, glass transition temperature of -27 ° C, weight average molecular weight of 660,000, molecular weight distribution curve measured by GPC is bimodal, its molecular weight distribution (PDI) is 1.5, styrene content is 43% by mass, vinyl content is 31%, and it is 25 parts by mass of oil-extended product.

[0111] SBR (B) -2: alkoxysilyl-terminated modified styrene butadiene rubber, F3420 produced by Asahi Kasei Corporation, glass transition temperature of -27°C, weight average molecular weight of 900,000, molecular weight distribution curve of GPC measurement is unimodal, molecular weight distribution (PDI) is 2.3, styrene content is 36% by mass, vinyl content is 40%, and it is 25 parts by mass of oil-extended product.

[0112] SBR (B) -3: an alkoxysilyl-terminated modified styrene butadiene rubber obtained by the following polymerization method, having a glass transition temperature of -31°C, a weight average molecular weight of 730,000, a single-peak molecular weight distribution curve when measured by GPC, a molecular weight distribution (PDI) of 1.3, a styrene content of 36% by mass, a vinyl content of 38%, and 20 parts by mass of an oil-extended product.

[0113] NR: natural rubber, SIR-20, glass transition temperature -62°C, weight average molecular weight 1.2 million.

[0114] Thermoplastic resin-1: Aromatic modified terpene resin, YS resin TO-125 produced by Yashara Chemical Co., Ltd., glass transition temperature 78°C

[0115] Thermoplastic resin-2: C9 resin, ENEOS Neopolymer S100, glass transition temperature 58°C

[0116] Resin-3: α-pinene resin, glass transition temperature 81°C, softening point 130°C, Mn 742 g / mol, Mz 1538 g / mol, Mw 1055 g / mol, Mw / Mn 1.42.

[0117] Resin-4: β-pinene resin, YS resin PX-1150N produced by Yashara Chemical Co., Ltd., glass transition temperature: 68°C

[0118] Resin-5: pinene resin (α-pinene 20% by mass, β-pinene 80% by mass), glass transition temperature 78°C, softening point 130°C, Mn 790 g / mol, Mz 1891 g / mol, Mw 1101 g / mol, Mw / Mn 1.57.

[0119] ·Carbon black: Carbon black produced by Kirin Corporation, Carbon Black N339, CTAB adsorption specific surface area is 90m 2 / g.

[0120] ·Silica: ZEOSIL1165MP produced by Solvay

[0121] Coupling agent-1: a silane coupling agent containing polysiloxane represented by the average composition formula of general formula (1), manufactured by Shin-Etsu Chemical Co., Ltd., average composition formula (-C3H6-S4-C3H6-) 0.071 (-C8H 17 ) 0.571 (-OC2H5) 1.50 (-C3H6SH) 0.286 SiO 0.75Represents polysiloxane.

[0122] · Coupling agent-2: In the general formula (2), R 2 ~R 4 is ethoxy, R 5 The silane coupling agent is n-heptyl, NXT Silane produced by Momentive, and 3-octanoylthio-1-propyltriethoxysilane.

[0123] · Coupling agent-3: silane coupling agent, Si69 produced by Evonik Degussa

[0124] ·Low aromatic oil: Esutech No. 4S produced by Semantec Co., Ltd.

[0125] SBR(A)-2 polymerization method

[0126] 70.0 g of cyclohexane and 0.77 mmol of tetramethylethylenediamine were added to an 800 ml ampoule bottle replaced with nitrogen, and 7.69 mmol of n-butyllithium was further added. Then 27.9 g of isoprene and 2.1 g of styrene were slowly added, and the reaction was carried out in the ampoule bottle at a temperature of 50° C. for 120 minutes to obtain a polymer block with an active terminal.

[0127] In an autoclave with a stirrer, 4000 g of cyclohexane, 1.50 mmol of tetramethylethylenediamine, 445 g of 1,3-butadiene and 155 g of styrene were added under a nitrogen atmosphere, and then all the above-obtained polymer blocks with active ends were added, and polymerization was started at 50°C. 10 minutes after the start of polymerization, 355 g of 1,3-butadiene and 40 g of styrene were added continuously for 60 minutes. The highest temperature during the polymerization reaction was 75°C. After the continuous addition was completed, the polymerization reaction was continued for another 10 minutes. After confirming that the polymerization conversion rate reached the range of 95% to 100%, 2.44 g of the polyorganosiloxane represented by the following formula (I) was added in the state of a 40% by mass concentration xylene solution, and it was reacted for 30 minutes. Then, methanol equivalent to 2 times the molar amount of n-butyl lithium used was added as a polymerization terminator to obtain a solution containing a conjugated diene rubber. To this solution, 0.15 parts of Ilganox 1520L (manufactured by BASF) as an antioxidant was added per 100 parts of the conjugated diene rubber, the solvent was removed by steam stripping, and the solution was vacuum dried at 60°C for 24 hours to obtain a solid conjugated diene rubber [SBR(A)-2].

[0128]

[0129] In the above formula (I), m is 80, k is 120, and X 1 , X 4 , R1 ~R 3 and R 5 ~R 8 is methyl, X 2 It is a group represented by the following formula (II) (here, * indicates a bonding position).

[0130]

[0131] Polymerization method of SBR(B)-3

[0132] Into the first reactor of the continuous reactor consisting of three reactors connected in series, a styrene solution of 60% by mass of styrene dissolved in n-hexane was injected at a rate of 6.5 kg / h, a 1,3-butadiene solution of 60% by mass of 1,3-butadiene dissolved in n-hexane was injected at a rate of 7.7 kg / h, n-hexane was injected at a rate of 47.0 kg / h, a 1,2-butadiene solution of 2.0% by mass of 1,2-butadiene dissolved in n-hexane was injected at a rate of 40 g / h, a solution of 10% by mass of N,N,N',N'-tetramethylethylenediamine (TMEDA) dissolved in n-hexane as a polar additive was injected at a rate of 50.0 g / h, and a modified initiator prepared in the following Preparation Example 1 was injected at a rate of 400.0 g / h. At this time, the temperature of the first reactor was maintained at 55° C., and the polymer was sent from the first reactor to the second reactor through the transfer pipe when the polymerization conversion rate reached 41%.

[0133] Then, a 1,3-butadiene solution prepared by dissolving 60% by mass of 1,3-butadiene in n-hexane was injected into the second reactor at a rate of 2.3 kg / h. At this time, the temperature of the second reactor was maintained at 65° C. When the polymerization conversion rate reached 95% or more, the polymer was transported from the second reactor to the third reactor through the transport pipe.

[0134] The polymer was transferred from the second reactor to the third reactor, and a solution (solvent: n-hexane) in which N-(3-(1H-1,2,4-triazol-1-yl)propyl)-3-(trimethoxysilyl)-N-(3-(trimethoxysilyl)propyl)propane-1-amine as a modifier was dissolved was continuously added to the third reactor [modifier: act.Li (polymerization initiator) = 1:1 mol]. The temperature of the third reactor was maintained at 65°C.

[0135] Then, a solution of IR1520 (manufactured by BASF) dissolved at 30% by mass as an antioxidant was injected at a rate of 170 g / h into the polymerization solution discharged from the third reactor and stirred. The resulting polymer was placed in warm water heated with steam and stirred to remove the solvent, thereby producing a modified conjugated diene polymer [modified SBR (B)-3].

[0136] [Manufacturing Example 1] Manufacture of modified initiator

[0137] Two vacuum-dried 4L stainless steel pressure vessels were prepared. 6922g of cyclohexane, 85g of the compound represented by the following chemical formula (i) and 60g of tetramethylethylenediamine were added to the first pressure vessel to prepare a first reaction solution. At the same time, 180g of 2.0M liquid n-butyllithium and 6926g of cyclohexane were added to the second pressure vessel to prepare a second reaction solution. At this time, the molar ratio of the compound represented by the chemical formula (i), n-butyllithium and tetramethylethylenediamine was 1:1:1. While maintaining the pressure of each pressure vessel at 7 bar, the first reaction solution was injected into the continuous reactor through the first continuous channel at an injection rate of 1.0g / min, and the second reaction solution was injected through the second continuous channel at an injection rate of 1.0g / min using a mass flow meter. At this time, the temperature of the continuous reactor was maintained at -10°C, and the internal pressure was maintained at 3 bar using a back pressure regulator, and the residence time in the reactor was adjusted to be within 10 minutes. After the reaction is completed, a modified initiator is obtained.

[0138]

[0139] Table 5

[0140]

[0141] The types of raw materials used in Table 5 are as follows.

[0142] Zinc oxide: 3 types of zinc oxide produced by Seonghwa Industries

[0143] · Stearic acid: Stearic acid YR manufactured by NOF Corporation

[0144] Anti-aging agent: Santoflex 6PPD produced by Solutia Europe

[0145] · Vulcanization accelerator-1: Nokusera CZ-G produced by Ouchi Shinko Chemical Co., Ltd.

[0146] · Vulcanization accelerator-2: Soxhinolu DG produced by Sumitomo Chemical Co., Ltd.

[0147] Sulfur: Jinhua ink-infused sulfur produced by Tsurumi Chemical Industry Co., Ltd.

[0148] As can be seen from Tables 3 to 4, the tire rubber compositions of Examples 1 to 16 can improve wear resistance, wet performance and low rolling resistance to levels higher than those of conventional ones, reduce the temperature dependence of low rolling resistance, and are also excellent in extrusion molding processability.

[0149] As can be seen from Table 1, the tire rubber composition of Comparative Example 1 has low wet performance because it does not contain a thermoplastic resin. In addition, the weight average molecular weight of the mixture composed of terminal modified styrene butadiene rubber (B) and natural rubber is less than 700,000, so the extrusion molding processability is poor.

[0150] The tire rubber composition of Comparative Example 2 contains a thermoplastic resin, but the weight average molecular weight of the mixture of terminally modified styrene butadiene rubber (B) and natural rubber is less than 700,000, so the extrusion molding processability is poor. In addition, the low rolling resistance cannot be improved.

[0151] In the tire rubber composition of Comparative Example 3, the total mass of the terminal-modified styrene butadiene rubber (B) and the natural rubber was less than 1 / 3 of the mass of the terminal-modified styrene butadiene rubber (A), so the extrusion molding processability was poor.

[0152] The rubber composition for a tire of Comparative Example 4 had a terminal-modified styrene-butadiene rubber (A) content of less than 50% by mass, and therefore had poor rolling resistance.

[0153] The tire rubber composition of Comparative Example 5 contained more than 30% by mass of natural rubber, and therefore was inferior in wet performance and rolling resistance.

[0154] In the tire rubber composition of Comparative Example 6, the terminal-modified styrene-butadiene rubber (A) exceeds 75% by mass, and the total mass of the terminal-modified styrene-butadiene rubber (B) and the natural rubber is less than 1 / 3 of the mass of the terminal-modified styrene-butadiene rubber (A), so the wet performance and extrusion molding processability are poor.

[0155] In the tire rubber composition of Comparative Example 7, the terminal-modified styrene-butadiene rubber (A) exceeds 75% by mass, and the total mass of the terminal-modified styrene-butadiene rubber (B) and the natural rubber is less than 1 / 3 of the mass of the terminal-modified styrene-butadiene rubber (A), so the extrusion molding processability is poor.

[0156] As can be seen from Table 2, in the tire rubber composition of Comparative Example 8, the total mass of the terminal-modified styrene butadiene rubber (B) and the natural rubber is less than 1 / 3 of the mass of the terminal-modified styrene butadiene rubber (A), so the extrusion molding processability is poor.

[0157] In the tire rubber composition of Comparative Example 9, since the silane coupling agent does not have a mercapto structure, the wet performance and rolling resistance are poor.

[0158] The tire rubber composition of Comparative Example 10 did not contain the terminal-modified styrene-butadiene rubber (A), and therefore had large rolling resistance and temperature dependence of rolling resistance, and also had low wear resistance. In addition, extrusion molding processability was poor.

[0159] The tire rubber composition of Comparative Example 11 contained less than 15 parts by mass of thermoplastic resin, and therefore had poor wet performance and extrusion molding processability.

[0160] Since the rubber composition for a tire of Comparative Example 12 contained more than 40 parts by mass of the thermoplastic resin, the rolling resistance was large and the temperature dependency of the rolling resistance was also large.

[0161] The rubber composition for a tire of Comparative Example 13 had less than 60 parts by mass of silica, so the wet performance was poor and the wear resistance was not improved.

[0162] Since the rubber composition for a tire of Comparative Example 14 contained more than 90 parts by mass of silica, the rolling resistance became larger and the wear resistance also decreased.

[0163] The present invention includes the following inventions.

[0164] Invention [1]. A rubber composition for a tire, characterized in that 60 to 90 parts by mass of silica and 15 to 40 parts by mass of a thermoplastic resin are blended into 100 parts by mass of a diene rubber containing a terminal-modified styrene butadiene rubber A and containing natural rubber and / or a terminal-modified styrene butadiene rubber B, and a silane coupling agent having a mercapto structure is blended in an amount of 2 to 15% by mass relative to the mass of the silica, wherein the terminal-modified styrene butadiene rubber A has a weight average molecular weight of 300,000 to 500,000 and a glass transition temperature of -50°C or less, the terminal-modified styrene butadiene rubber B has a weight average molecular weight of 600,000 or more, the weight average molecular weight of a mixture of the terminal-modified styrene butadiene rubber B and natural rubber is 700,000 or more, and the average glass transition temperature of the diene rubber is -50°C or less,

[0165] In 100% by mass of the diene rubber, the terminal-modified styrene butadiene rubber A accounts for 50 to 75% by mass, the natural rubber accounts for 0 to 30% by mass, and the total mass of the terminal-modified styrene butadiene rubber B and the natural rubber is 1 / 3 or more of the mass of the terminal-modified styrene butadiene rubber A.

[0166] Invention [2]. The tire rubber composition according to Invention [1], wherein the terminal-modified styrene butadiene rubber B has a single-peak molecular weight distribution curve when measured by gel permeation chromatography, and its molecular weight distribution PDI is less than 1.7.

[0167] Invention [3]. The tire rubber composition according to Invention [1] or [2], wherein the terminal-modified styrene-butadiene rubber B contains 0 to 50% by mass in 100% by mass of the diene rubber.

[0168] Invention [4]. A tire rubber composition as described in any one of Inventions [1] to [3], characterized in that the thermoplastic resin contains 25% by mass or more of a terpene resin, and when the terpene resin contains units derived from α-pinene, the content of the units derived from α-pinene is 60% by mass or less.

[0169] Invention [5]. The tire rubber composition according to any one of Inventions [1] to [4], wherein the thermoplastic resin has a glass transition temperature of 40°C to 120°C.

[0170] Invention [6]. The tire rubber composition according to any one of Inventions [1] to [5], wherein the thermoplastic resin is at least one resin selected from the following resins and resins in which at least a portion of the double bonds of these resins are hydrogenated:

[0171] The resin is terpene, modified terpene, rosin, rosin ester, or a resin composed of at least one selected from C5 components and C9 components.

[0172] The glass transition temperature of the thermoplastic resin is 40 to 120°C.

[0173] Invention [7]. A tire having a tread portion made of the tire rubber composition according to any one of Inventions [1] to [6]

[0174] 1. Tread

[0175] 2. Sidewall

[0176] 3 Bead section

[0177] 4 carcass layers

[0178] 5 bead core

[0179] 6. Rubber filling for tire bead

[0180] 7 Lining layer

[0181] 8 belt layer

[0182] 9 belt cover

[0183] 10a tread crown

[0184] 10b tread base

Claims

1. A rubber composition for a tire, characterized in that: In 100 parts by mass of a diene rubber containing terminal-modified styrene butadiene rubber A and containing natural rubber and / or terminal-modified styrene butadiene rubber B, 60 to 90 parts by mass of silica and 15 to 40 parts by mass of a thermoplastic resin are mixed, and a silane coupling agent having a mercapto structure is mixed in an amount of 2 to 15% by mass relative to the mass of the silica, wherein the terminal-modified styrene butadiene rubber A has a weight average molecular weight of 300,000 to 500,000 and a glass transition temperature of -50°C or less, the terminal-modified styrene butadiene rubber B has a weight average molecular weight of 600,000 or more, the weight average molecular weight of a mixture of the terminal-modified styrene butadiene rubber B and natural rubber is 700,000 or more, and the average glass transition temperature of the diene rubber is -50°C or less, In 100% by mass of the diene rubber, the terminal-modified styrene butadiene rubber A accounts for 50 to 75% by mass, the natural rubber accounts for 0 to 30% by mass, and the total mass of the terminal-modified styrene butadiene rubber B and the natural rubber is 1 / 3 or more of the mass of the terminal-modified styrene butadiene rubber A.

2. The tire rubber composition according to claim 1, wherein The terminal-modified styrene butadiene rubber B has a single peak in a molecular weight distribution curve when measured by gel permeation chromatography, and its molecular weight distribution PDI is less than 1.

7.

3. The tire rubber composition according to claim 1 or 2, wherein: The terminal-modified styrene-butadiene rubber B is contained in an amount of 0 to 50% by mass in 100% by mass of the diene rubber.

4. The tire rubber composition according to claim 1 or 2, wherein: The thermoplastic resin contains 25% by mass or more of a terpene resin, and when the terpene resin contains a unit derived from α-pinene, the content of the unit derived from α-pinene is 60% by mass or less.

5. The tire rubber composition according to claim 1 or 2, wherein: The glass transition temperature of the thermoplastic resin is 40°C to 120°C.

6. The tire rubber composition according to claim 1 or 2, characterized in that: The thermoplastic resin is at least one selected from the following resins and resins in which at least a part of the double bonds of these resins are hydrogenated: The resin is terpene, modified terpene, rosin, rosin ester, or a resin composed of at least one selected from C5 components and C9 components. The glass transition temperature of the thermoplastic resin is 40 to 120°C.

7. A tire having a tread portion made of the rubber composition for a tire according to claim 1 or 2.

Citation Information

Patent Citations

  • Tire rubber composition

    JP2013227375A